A practical theoretical formalism for atomic multielectron processes: direct multiple ionization by a single auger decay or by impact of a single electron or photon. (16th March 2018) - Liu, Pengfei; Zeng, Jiaolong; Yuan, Jianmin
Abstract: Multiple electron processes occur widely in atoms, molecules, clusters, and condensed matters when they are interacting with energetic particles or intense laser fields. Direct multielectron processes (DMEP) are the most complicated among the general multiple electron processes and are the most difficult to describe theoretically. In this work, a unified and accurate theoretical formalism is proposed on the DMEP of atoms including the multiple auger decay and multiple ionization by an impact of a single electron or a single photon based on the atomic collision theory described by a correlated many-body Green's function. Such a practical treatment is made possible by taking consideration of the different coherence features of the atoms (matter waves) in the initial and final states. We first explain how the coherence characteristics of the ejected continuum electrons is largely destructed, by taking the electron impact direct double ionization process as an example. The direct double ionization process is completely different from the single ionization where the complete interference can be maintained. The detailed expressions are obtained for the energy correlations among the continuum electrons and energy resolved differential and integral cross sections according to the separation of knock-out (KO) and shake-off (SO) mechanisms for the electron impact direct double ionization, direct double and triple auger decay, and double and triple photoionization (TPI) processes. Extension to higher order DMEP than triple ionization is straight forward by adding contributions of the following KO and SO processes. The approach is applied to investigate the electron impact double ionization processes of C +, N +, and O +, the direct double and triple auger decay of the K-shell excited states of C + 1 s 2 s 2 2 p 2 2 D and 2 P, and the double and TPI of lithium. Comparisons with the experimental and other theoretical investigations wherever available in the literature show that our theoretical formalism is accurate and effective in treating the atomic multielectron processes.